2023
DOI: 10.1007/s00268-023-07142-x
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Primary Treatment for Colorectal Cancer After Implementation of National Screening: A Nationwide Cohort Study

Jannie Dressler,
Sisse H. Njor,
Lars N. Jørgensen
et al.

Abstract: Background The effect of organized colorectal cancer (CRC) screening on type of primary treatment remains sparsely investigated. This study evaluated the difference in primary treatment strategy between patients diagnosed with screen-detected (SD-CRC) and non-screen-detected colorectal cancer (NSD-CRC) in a national CRC screening program. Methods This was a retrospective national register-based cohort study. Data on patients aged between 50 and 75 years and diagnosed with SD-CRC or NSD-CRC were retrieved from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…There is evidence that the rate of open surgery for patients with SD-CRC is lower 16–18 . A study conducted on the same population reported a significantly higher chance of minimally invasive surgery for patients with SD-CRC (RR 1.16) and this difference was consistent across all UICC stages 35 . This surgical practice would be expected to contribute to a reduction in postoperative complications and mortality 19–21 .…”
Section: Discussionmentioning
confidence: 70%
“…There is evidence that the rate of open surgery for patients with SD-CRC is lower 16–18 . A study conducted on the same population reported a significantly higher chance of minimally invasive surgery for patients with SD-CRC (RR 1.16) and this difference was consistent across all UICC stages 35 . This surgical practice would be expected to contribute to a reduction in postoperative complications and mortality 19–21 .…”
Section: Discussionmentioning
confidence: 70%